Functional demonstration of plant flavonoid carbocations proposed to be involved in the biosynthesis of proanthocyanidins. (6th October 2019) - Wang, Peiqiang; Liu, Yajun; Zhang, Lingjie; Wang, Wenzhao; Hou, Hua; Zhao, Yue; Jiang, Xiaolan; Yu, Jie; Tan, Huarong; Wang, Yunsheng; Xie, De‐Yu; Gao, Liping; et al.
Summary: The plant flavonoid dogma proposes that labile plant flavonoid carbocations (PFCs) play vital roles in the biosynthesis of proanthocyanidins (PAs). However, whether PFCs exist in plants and how PFCs function remain unclear. Here, we report the use of an integrative strategy including enzymatic assays, mutant analysis, metabolic engineering, isotope labeling and metabolic profiling to capture PFCs and demonstrate their functions. In anthocyanidin reductase (ANR) assays, an (−)‐epicatechin conjugate was captured in protic polar nucleophilic methanol alone or methanol−HCl extracts. Tandem mass spectrum (MS/MS) analysis characterized this compound as an (−)‐epicatechin‐4‐ O ‐methyl (EOM) ether, which resulted from (−)‐epicatechin carbocation and the methyl group of methanol. Acid‐based catalysis of procyanidin B2 and B3 produced four compounds, which were annotated as two EOM and two (+)‐catechin‐4‐ O ‐methyl (COM) ethers. Metabolic profiling of seven PA pathway mutants showed an absence or reduction of two EOM ether isomers in seeds. Camellia sinensis ANRa ( CsANRa ), leucoanthocyanidin reductase c ( CsLARc ), and CsMYB5b (a transcription factor) were independently overexpressed for successful PA engineering in tobacco. The EOM ether was remarkably increased in CsANRa and CsMYB5b transgenic flowers. Further metabolic profiling for eight green tea tissues revealed two EOM and two COM ethers associated with PA biosynthesis. Moreover, an incubation of (−)‐epicatechin or (+)‐catechin with epicatechin carbocation in CsANRa transgenic flower extracts formed dimeric procyanidin B1 or B2, demonstrating the role of flavan‐3‐ol carbocation in the formation of PAs. Taken together, these findings indicated that flavan‐3‐ol carbocations exist in extracts and are involved in the biosynthesis of PAs of plants. Significance Statement: Although the dogma of plant flavonoids proposes that labile plant flavonoids carbocations (PFCs) exist to associate with the biosynthesis of proanthocyanidins (PAs), supportive evidence is lacking. Data from biochemical analysis, isotope labeling, genetic analysis, metabolic engineering and metabolic profiling demonstrate that PFCs are involved in the biosynthesis of PAs.